Kebijakan Penerapan Standar Akuntansi Keuangan Nomor 8 Dan 71 dalam Laporan Keuangan CV.SKU Masa dan Pasca Pandemi Covid-19 - Endah Sulistyowati; Agung Kristiawan; Lydia Setyawardanil; Mega Arisia Dewi (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to analyze and evaluate PSAK number 55 to switch to follow the policy of implementing PSAK number 8 and 71. Financial instruments required by the IAI Accounting Standards Board are effective as of January 1, 2020 which have not been practiced in the preparation of 2021 CV. SKU’s Financial Statements. Descriptive comparative qualitative study. Trading companies must leave and return from Umrah and Hajj. Data collecting via observing, interviewing, and documenting informants. According to conversations with CV.SKU's accounting and receivables administration department, its financial statements have not implemented the new policy and are still in compliance with PSAK number 55 taxable. Recalculating fair value data for financial statements is offered as a unit of study from literature books and journals of earlier researchers, paying attention to PSAK standards number 8 and 71 financial instruments. The results showed that applying PSAK number 8 and 71 to the statement of financial position account resulted in a reserve account for receivables losses, deferred tax asset accounts, decreased retained profit, and decreased CV. SKU assets. The impairment loss reserve appears as an accounts receivable loss expenditure account in the income statement, creating a deferred tax advantage account. Financial statements prepared according to IAI Financial Accounting Standards Board requirements are presented properly.